Competency and Creativity as A Relationship That Interpretes Between the Perception of An Organizational Support on Performance of The Craftsman of Ikat Endek In Klungkung Bali - Saraswati, Ni Putu Ayu Sintya; Putra, Gde Bagus Brahma (Asia Pacific Journal of Management and Education (APJME), 2020)
This study aims to analyze the influence of competence and creativity as a relationship that mediates between perceptions of organizational support for the performance of endek weaving craftsmen in Klungkung Regency, Bali Province. The population in this study was 1372 employees, with a sample of 93 respondents. Sampling using accidental sampling technique. The data analysis used in this study is descriptive analysis and Structural Equation Modeling (SEM) PLS. The results of the study show: 1) perceptions of organizational support have a positive and significant effect on competence. 2) perceptions of organizational support have a positive and significant effect on creativity. 3) perception of organizational support has a positive and significant effect on performance.